Akibat Hukum atas Pelanggaran Sistem Pernikahan Endogami di Indonesia: Studi Peraturan Perundang-Undangan - Agussalim A. Gadjong (SIGn Jurnal Hukum, 2023)
This study aims to examine and analyze how sanctions are applied for violating the endogamous marriage system and linked in the context of the positive law system in Indonesia. This study uses normative legal research with conceptual, historical, and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show sanctions and consequences for individuals violating the endogamous marriage system. Sanctions can range from social ostracism, status demotion to fines and withdrawal of access to resources. In religious endogamy, violations are considered sins, and marriages can be declared invalid under Law Number 1 of 1974. Violations of racial or ethnic and caste endogamy do not have formal legal consequences but can impact an individual’s social status. Therefore, it is recommended that authorities and community leaders continue educating individuals about the implications of these endogamous marriage systems. The need for open dialogues about the pros and cons of these systems is also essential. Furthermore, the Indonesian legal system should protect all individuals’ rights and uphold principles of equality and non-discrimination while respecting cultural and religious nuances.